Comparison Of Hysteroscopic Myomectomy Versus Medical Management For Menorrhagia In Submucosal Fibroids: Systematic Review Of Randomized Trials And Observational Studies (The Review of Diabetic Studies, 2025)
Background: Heavy menstrual bleeding (HMB) from submucosal (FIGO 0–2) fibroids is a major cause of anemia and impaired quality of life. Whether hysteroscopic myomectomy offers superior patient-important outcomes to medical therapy remains uncertain.Objective: To compare the effectiveness, safety, durability, and patient-centered outcomes of hysteroscopic myomectomy versus medical management for HMB caused by submucosal fibroids.Study eligibility criteria: Randomized trials and comparative observational studies enrolling premenopausal women with imaging- or hysteroscopy-confirmed submucosal fibroids and HMB. Interventions included hysteroscopic myomectomy versus medical therapies (e.g., LNG-IUS, combined or progestin-only hormones, tranexamic acid/NSAIDs, GnRH analogs/antagonists, SPRMs). Primary outcome: reduction in menstrual blood loss (objective volume or PBAC and controlled bleeding). Secondary outcomes: hemoglobin/ferritin, quality of life (UFS-QOL& MMAS/SF-36), reintervention/hysterectomy, adverse events, fertility, satisfaction, and costs.Methods: Dual independent screening and extraction; RoB 2 for randomized trials and ROBINS-I for observational studies; prespecified random-effects meta-analysis and GRADE certainty assessment.Results: Two comparative studies met criteria (one randomized trial, one prospective cohort). No eligible study reported head-to-head PBAC/MBL, precluding pooling for the primary endpoint. The randomized trial showed clinically meaningful improvements in both groups, with larger domain-level UFS-QOL gains after hysteroscopic myomectomy; the total score difference was imprecise. Short-term serious adverse events were uncommon across arms. Long-term reintervention, hysterectomy, hemoglobin, fertility, and cost outcomes were sparsely reported. Overall certainty ranged from low to very low due to imprecision, outcome heterogeneity, and risk of bias.Conclusions: Hysteroscopic myomectomy and medical therapy both improve symptoms; short-term quality-of-life gains may be greater after myomectomy in appropriately selected patients. Robust head-to-head trials using standardized bleeding outcomes and longer follow-up including fertility and durability are needed.